Finite element stress analysis of squeeze-off of polyethylene pressure pipes - YAYLA, PAŞA (My University, 2024)
In this study, the stress analysis of PE 100 grade high-density polyethylene pressure pipe squeeze-off has been carried out using ABAQUS, a general-purpose finite element code. The squeeze-off phenomenon has been investigated for the single and double squeeze-off pipes. In the finite element analysis, the true stress-strain curve of the material has been adopted. The stress distributions in the squeezed pipe have been obtained. Special attention has been paid to the axial and von Mises stress distributions along the pipe axis and around the squeeze-off ear. Finally, the practical implications of the axial stress and von Misses stress distributions resulting from the squeeze-off phenomenon have been discussed and correlated with the minimum distance away from the pipe welds, mechanical connections, local saddle joints, or nearest squeeze-off locations imposed by related standards.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; Genel Malzeme Bilimi; Fizik Bilimleri; Genel Mühendislik; General Materials Science; Physical Sciences; General Engineering; Finite element modelling; Pipe failure; Pipe stresses; Polyethylene pipes; Squeeze-off